Plan Estratégico para el Colegio “Galo Plaza Lasso” de la Parroquia Capiro, Cantón Piñas, Provincia de El Oro periodo 2017 – 2021 - Maldonado Loaiza, José Miguel (2017)
The present investigativo work is a proposal that was elaborated like instrument of support for the attainment of objectives; it made the processes of the planning, organization, direction and control; the main intention is to offer to the school a strategic planning period 2017 - 2021, agreed to its necessities and plans of improvement, with which one looks for to obtain a development at academic level, institutional and in infrastructure. The obtained results are in narrow relation with the proposed objectives, where its accomplishment by means of an internal and external diagnosis is shaped to determine the present situation, soon the construction of matrix FODA on the basis of matrices EFE and EFI was made to take step finally to the action plan that consists of the improvement proposal: mission, vision, organizational charts, strategies, activities, responsibilities and indicators that contributed in the elaboration of the annual operative plans (POA). The methods and techniques used for the development of this investigation were: inductive, that was used it to know the situation real the institution; analytical - synthetic, it helped to classify, to analyze all the information and to take step to the formulation of strategic targets; deductive, it allowed to establish the characteristics of the administrative processes and management. By means of which it was managed to develop the stages of the strategic planning, initiating with the determination of the present situation analysis until its formulation of strategies like administrative tools. Within the conclusions, it is emphasized that the educative unit lacks an administrative process which pronounces by means of the lack of a structured mission and affluent vision, does not have a structural organizational chart, limitantes in infrastructure and equipment of laboratories. Finally, it is recommended that the institution takes into account the planning strategic propose as a tool fundamental from aid to establish goals and objectives able to reach the proposed institutional aims.